Hairy Rove Beetle Creophilus maxillosus (Linnaeus) (Insecta: Coleoptera: Staphylinidae) - Nicolas Johsnton; Philip Stansly; Andrea Lucky (EDIS)
This document provides an overview of the hairy rove beetle, Creophilus maxillosus, detailing its identification, distribution, life cycle, and ecological significance. The beetle is recognized for its distinctive yellowish-gray setae and its role as a predator of pest fly larvae. Found globally, it inhabits various environments and is beneficial in forensic entomology for determining post-mortem intervals. Despite occasional urban infestations, the beetle is valued for biological control in agriculture. The article also discusses its defensive mechanisms and the importance of understanding its life cycle for effective pest management.